2021
DOI: 10.1039/d1dt00953b
|View full text |Cite
|
Sign up to set email alerts
|

Non-palindromic (C^C^D) gold(iii) pincer complexes are not accessible by intramolecular oxidative addition of biphenylenes – an experimental and quantum chemical study

Abstract: We herein report on the synthesis of biphenylenes substituted with a pyridine (N), a phosphine (P) and a carbene (C’) donor as well as a carbene donor with additional pyridine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…rely on the dibenzostannol route in order to access sets of LAu­(bph)­Cl complexes. ,, This demonstrates that for screenings, it is more convenient and effective to add a library of ligands to a single gold precursor, instead of preparing all corresponding LAu­(I)Cl complexes followed by oxidative addition to biphenylene. Recently, it was also reported that the attempted directed oxidative addition to a biphenylene derivate failed to give (C ∧ C ∧ D)­Au­(III) complexes, while a stannane-based synthesis has been successfully implemented for the synthesis of highly luminescent tridentate (C ∧ C ∧ D)­Au­(III) complexes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…rely on the dibenzostannol route in order to access sets of LAu­(bph)­Cl complexes. ,, This demonstrates that for screenings, it is more convenient and effective to add a library of ligands to a single gold precursor, instead of preparing all corresponding LAu­(I)Cl complexes followed by oxidative addition to biphenylene. Recently, it was also reported that the attempted directed oxidative addition to a biphenylene derivate failed to give (C ∧ C ∧ D)­Au­(III) complexes, while a stannane-based synthesis has been successfully implemented for the synthesis of highly luminescent tridentate (C ∧ C ∧ D)­Au­(III) complexes …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was also reported that the attempted directed oxidative addition to a biphenylene derivate failed to give (C ∧ C ∧ D)Au(III) complexes, 15 while a stannane-based synthesis has been successfully implemented for the synthesis of highly luminescent tridentate (C ∧ C ∧ D)Au(III) complexes. 16 While the bph-tin species can be isolated under air, 10b organotin compounds are known to degrade by light and atmospheric oxygen over time, complicating their storage and handling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, recent work by Breher and co-workers showcased the difficulty of achieving such a transformation. 10 …”
mentioning
confidence: 99%
“… 14 The choice of a neutral weakly bound gold( i )-iodide precursor is key for a successful reaction outcome: similar reactions in the presence of [(NHC)AuCl + AgSbF 6 ] failed to deliver the desired biscyclometalation adducts, as reported by Breher et al in ref. 10 . The oxidative insertion of gold( i ) iodide into the four-membered ring of pyridino-substituted biphenylene provides a novel and synthetically efficient entry to κ 3 -(N^C^C)gold( iii ) halides.…”
mentioning
confidence: 99%
See 1 more Smart Citation